Data Exfiltration in IoT Protocols - Uroz, Daniel; Rodríguez, Ricardo J. (Jornada de Jóvenes Investigadores del I3A, 2020)
We investigated how IoT protocols can be used for data exfitration. We theoretically define how they can be used to exfiltrate data and we compare them to traditional protocols. Finally, we present the Python library chiton and we empirically measure the data exfiltration elapsed time for different amounts of data.